179k views
1 vote
What is the step by step equation for

What is the step by step equation for-example-1

2 Answers

5 votes

Explanation:

this might be the answer

What is the step by step equation for-example-1
User Tomazi
by
5.6k points
4 votes

Answer:

First, know that
csc(x)=(1)/(sin(x)):


(1)/(sin^(2)(x)) *cos^(2)(x)=(cos^(2)(x))/(sin^(2)(x))

Remember that cos²(x) + sin²(x) = 1, so cos²(x) = 1 - sin²(x):


(cos^(2)(x))/(sin^(2)(x)) =(1-sin^(2)(x))/(sin^(2)(x)) =(1)/(sin^(2)(x)) -(sin^(2)(x))/(sin^(2)(x)) =csc^(2)(x)-1

User William Lepinski
by
4.4k points